PEMBUATAN ROTARY MIXER UNTUK PENCAMPURAN PARTIKEL KAYU DENGAN PEREKAT - Anhar Firdaus (Kementerian Perindustrian, 2010)
One of the important auxiliary processes in the wood processing industry, especially making particle board or fiberboard is gluing. Bonding process is influenced by the type of adhesive material, process and place of gluing, apart from the nature of the taped material. Until now, the adhesive material commonly used include synthetic adhesive Urea Formaldehyde (UF), Phenol Formaldehyde (PF) or Melamine Formaldehyde (MF).The rotary mixer is designed in a simple to mixing between partiket with glue that adhesion earns homogen. Rotary mixer has 5 (five) major units, namely: the framework tools (foundation), tubes mixing, mixer circuit, drive circuit and compressor. The working principle of this tool is stirring directly between the wood particles with adhesive. Material in the form of wood particles (after a specified weight) is inserted first into the mixing tube. Once the machine is turned on, a series of rotating stirrer will stir load (material particles). The next process is to insert adhesive into the tube, either by spraying or directly poured slowly little by little. Key wood : particles, adhesive, rotary mixer.